`f(x)=cosh(8x+ 1)`

Take note that the derivative formula of cosh is

`d/dx[cosh(u)] = sinh(u) *(du)/dx`

Applying this formula, the derivative of the function will be

`f'(x) = d/dx [cosh(8x+1)]`

`f'(x) = sinh(8x + 1)*d/dx(8x+1)`

`f'(x)=sinh(8x + 1) * 8`

`f'(x) = 8sinh(8x +1)`

** Therefore, the derivative of the function...**

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`f(x)=cosh(8x+ 1)`

Take note that the derivative formula of cosh is

`d/dx[cosh(u)] = sinh(u) *(du)/dx`

Applying this formula, the derivative of the function will be

`f'(x) = d/dx [cosh(8x+1)]`

`f'(x) = sinh(8x + 1)*d/dx(8x+1)`

`f'(x)=sinh(8x + 1) * 8`

`f'(x) = 8sinh(8x +1)`

**Therefore, the derivative of the function is `f'(x) =8sinh(8x+1)` .**